STUDY ON ANXIETY AND SELECTED PHYSIOLOGICAL VARIABLES OF AGED SCHOOL-TEACHERS (Journal of Pharmaceutical Negative Results, 2022)
Introduction:Anxiety is the natural response of our body against chronic stress It is normal to feel anxious at some moments. But people with anxiety disorder feel the same type of feelings all the time. The purpose of the study was to find out the relation of anxiety level and some selected physiological factors of aged school-teachers.Materials and Methods: For the present study the researcher randomly selected 80 school teachers. Among them 40 were male(Average 50.725 years) and 40 were female (Average 51.125 years). The Anxiety level was measured by a standardized set of questionnaire. The physiological variables were blood glucose level-PP(mg/dl), heart rate(b/m), systolic blood pressure (mmHg), diastolic blood pressure (mmHg)and BMI (Kg/M2).Coefficient of correlation of physiological variables with Stress level was calculated at 0.05 level of significance.Results and Discussion:The result showed the coefficient of correlation ofBlood Glucose Level, Heart Rate, Systolic Blood Pressure, Diastolic Blood Pressure and BMI with Anxiety was 0.313, 0.198, 0.467, 0.307 and 0.398in case of male teachers and 0.344, 0.338, 0.310, 0.423 and 0.369 in case of female teachers subsequently.In the present study it was found that all the variables showed a positive coefficient of correlation with anxiety level of the aged school-teachers.Conclusion:From the above discussion it may be concluded that persons with high anxiety level have high Blood Glucose Level, Heart Rate, Blood Pressure and BMI; and persons with less anxietylevel have low Blood Glucose Level, Heart Rate, Blood Pressure and BMI.